Gastric schwannoma with giant ulcer and lymphadenopathy mimicking gastric cancer: a case report - Tang, Caihua (BMC Gastroenterol, 2020)
BACKGROUND: Gastric schwannomas are rare benign tumors originating from the intramuscular plexus of the stomach and account for just 2.6% of gastric mesenchymal tumors. Gastric schwannoma (GS) with a surface ulcer is very rare. Herein, we report a rare case of an ulcer-bearing GS, which in conjunction with multiple enlarged regional lymph nodes, readily mimicked gastric cancer (GC). CASE PRESENTATION: A 79-year-old female presented with poor appetite and intermittent vomiting of gastric contents during the past month. Gastroscopy revealed a giant crateriform ulcer within the stomach body (at the angular notch). Its raised and indurated border was fragile and bled easily. GC was thus suspected. Contrast-enhanced computer tomography (CT) revealed a mild enhancement of the corresponding irregularly thickened gastric wall, and an annular zone of mucosal discontinuity. Enlarged regional lymph nodes were also found, making GC with metastases of lymph nodes our primary concern. (18)F-fluorodeoxyglueose position emission tomography ((18)F-FDG PET)/CT was then performed for further staging. Obviously increased FDG uptake was shown in the gastric lesion ((maximum standardized uptake value (SUV(max)) 14.6), but no FDG uptake was observed in the enlarged regional lymph nodes. Given the strong suspicion of GC, subtotal gastrectomy was performed. GS was revealed by postoperative pathology, with no evidence of metastasis in the 13 resected lymph nodes. CONCLUSIONS: This was a rare case of GS with a giant surface ulcer and multiple enlarged regional lymph nodes. The uptake of (18)F-FDG in the tumor was substantially higher than previously published literature reports. Under these circumstances, it is difficult to be differentiated from GC.